2000
DOI: 10.1016/s0168-583x(99)00674-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ultra thin oxynitrides: A general approach

Abstract: The determination of nitrogen depth pro®les in thin oxynitride layers (1.5±3 nm) becomes more and more important in microelectronics. The goal of this paper is to investigate a methodology for the characterization of thin oxynitride layers with the aim to establish in a quantitative manner the layer thickness, N-content and detailed N-depth pro®le. For this study ultra thin oxynitride ®lms of 2.5 nm on Si were grown by oxygen O 2 annealing of Si followed by a NO annealing. The global ®lm characteristics were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Habraken and colleagues examined N, O, Si, and H using ERD of primary MeV ions. 37,225 More recently, Brijs 242 241 is shown in Fig. 30.…”
Section: Ion Beam Analysismentioning
confidence: 95%
“…Habraken and colleagues examined N, O, Si, and H using ERD of primary MeV ions. 37,225 More recently, Brijs 242 241 is shown in Fig. 30.…”
Section: Ion Beam Analysismentioning
confidence: 95%
“…The same oxynitride sample was also analysed in a small round-robin study with different techniques: lowenergy dynamic SIMS, XPS, HRBS (High resolution Rutherford Backscattering Spectrometry), HERD (High resolution Elastic Recoil Detection), etc. 5,10,17 Based on this study and the intensity (corrected area), mass resolution (MR) and interference (Table 1) of the different nitrogen clusters in our ToF-SIMS profile (Fig. 1), we concluded that the Si 2 N C signal corresponds to the observation of HERD, where nitrogen was clearly detected at the interface.…”
Section: Selection Of Nitrogen Clusters and Interface Determinationmentioning
confidence: 68%
“…The most commonly known are: Transmission Electron Microscopy (TEM) combined with electron dispersive spectroscopy and/or Electron Energy Loss Spectroscopy (EELS) [11]; nuclear techniques such as highresolution Rutherford Backscattering Spectrometry (HR-RBS) [12], Medium Energy Ion Scattering (MEIS) [13] or Elastic Recoil Detection (ERD) [14]; Time-of-Flight (TOF), Secondary Ion Mass Spectroscopy (SIMS) [15] and Angle-Resolved X-ray Photoelectron Spectroscopy (ARXPS) [12,[16][17][18].…”
Section: Theory Concerning Measurement Of Nanolayer Thicknessmentioning
confidence: 99%